Analysis of The Infulence of Practical-Based Reaction Rate learning on Students’ Science Process Skills - Rahmi, Chusnur (MANDAILING GLOBAL EDUKASIA, 2025)
Practicum as an important part of the chemistry learning process, trains and develops students' scientific process skills in testing chemical theories. The low science process skills cause students to struggle with understanding work procedures, processing data, and concluding experimental results. This study aims to determine the effect of reaction rate practicum on students' science process skills. This study uses a quantitative approach with a quasi-experimental nonequivalent control group design method. The research sample involved 35 students from class XI-MIPA 1 in the experimental class and 35 students from class XI-MIPA 3 in the control class at MAN 3 Aceh Barat Daya. Research data were collected using observation sheets to measure science process skills and multiple-choice tests to measure the impact of practicum on science process skills. The research results show that the science process skills of students in the experimental class are better compared to the control class. Students demonstrated very good observation and good skills in classifying, asking questions, and hypothesizing. However, they have sufficient skills in interpreting and communicating. The results of the hypothesis test obtained a t-value of 2.67 > t-table 1.65 at a significance level of 0.05, indicating that the implementation of practicum significantly affects students' science process skills in reaction rate learning. An effect size score of 0.18 indicates that practical-based reaction rate learning has a significant impact on students' science process skills. It is concluded that the reaction rate practicum influences the development of students' science process skills at MAN 3 Aceh Barat Daya.